The Receiver of the Agrobacterium tumefaciens VirA Histidine Kinase Forms a Stable Interaction with VirG to Activate Virulence Gene Expression - Wise, Arlene A.; Binns, Andrew N. (Frontiers in Microbiology, 2016)
The plant pathogen Agrobacterium tumefaciens carries a virulence gene system that is required for the initiation of crown gall tumors on susceptible plants. Expression of the vir genes is activated by the VirA/VirG two component regulatory system. VirA is a histidine kinase which signals the presence of certain chemicals found at the site of a plant wound. The receiver domain located at its carboxyl terminus defines VirA as a hybrid histidine kinase. Here, we show that the VirA receiver can interacts with the DNA-binding domain of VirG. This finding supports the hypothesis that the receiver acts as a recruiting factor for VirG. In addition, we show that removal of the VirA receiver allowed vir gene expression in response to glucose in a dose dependent manner, indicating that the receiver controls VirG activation and suggesting that the supplementary ChvE-sugar signal increases this activity.